G Protein-Coupled Receptor 109A Maintains the Intestinal Integrity and Protects Against ETEC Mucosal Infection by Promoting IgA Secretion - Gong, Yuhong; Jin, Xinxin; Yuan, Boyu; Lv, Yantao; Yan, Guangmou; Liu, Mingming; Xie, Changxin; Liu, Juxiong; Tang, Yimei; Gao, Hongyan; Zhu, Yufeng; Huang, Yanhua; et al. (Frontiers in Immunology, 2021)
More and more studies have shown that GPR109A is closely related to intestinal health. After being activated by butyric acid and β-hydroxybutyric acid, GPR109A regulates the expression of tight junction proteins, exerts anti-inflammatory effects, and maintains the integrity of the intestinal barrier. Nonetheless, the role and mechanism of GPR109A in the infection of exogenous pathogenic microorganisms is still unclear. In this article, we established an animal model of infection by oral ETEC gavage to observe the protect effect of GPR109A on the intestinal tract and the mechanisms underlying. Experimental GPR109A-/- and GPR109A+/+ mice were administered with 1×109 CFU ETEC by oral administration. Body weight changes were observed. The colonization and translocation of ETEC in the intestine were detected by plate counting method. The expression of tight junction protein, inflammatory factor and SIgA in the intestine were detected by q-PCR, western blot, ELISA and Immunohistochemistry. The results showed that GPR109A-/- mice were more susceptible to ETEC infection, showing more severe inflammatory reactions and intestinal damage. It is worth noting that the secretion of IgA in the intestinal tract of GPR109A+/+ mice was significantly increased after ETEC infection, while the IgA level of GPR109A-/- mice did not change significantly. Adding 5 g/L sodium butyrate into drinking water can pre-protect GPR109A+/+ mice against ETEC infection, but has no effect on GPR109A-/- mice. Similarly, sodium butyrate increased the SIgA content in the gut of the GPR109A+/+ mice, but not GPR109A-/- mice. In conclusion, activated GPR109A is effective against colonization and translocation of ETEC in the gut and maintains intestinal barrier integrity, possibly by the promotion of intestinal IgA secretion.